Storytelling como ferramenta de discurso no Twitter: uma análise da campanha presidencial de Jair Bolsonaro em 2018 - Pereira, Matheus Ribeiro (2021)
Understanding Creative Economy as an interdisciplinary field, this research analyzes technological transformations as important aspects in the construction of political narratives. Taking into account the advances of social media platforms in the recent elections, we sought to investigate the storytelling as a tool for narrowing engagement between candidate and potential voters in the digital universe. It was selected as a case study the presidential campaign of Jair Messias Bolsonaro, in the year 2018, since the time of the candidate’s televised campaign was, approximately, 8 seconds what leading him to act more incisively on social media. Twitter was chosen as a platform to be analyzed because Bolsonaro declared, on several occasions, make use of this space as a virtual platform announcing government proposals, countering criticism and carrying out attacks on the opposition. The interest of this study was, specifically, to describe the profile of potential voters identified with the movement of the new right in Brazil from surveys conducted by Datafolha (2018) and Ibope (2018), in addition to data collected by the Center for Urban and Audiovisual Ethnography of the Fundação Escola de Sociologia e Política de São Paulo (2018); analyze the speeches of the tweets of Bolsonaro, between 11 September and 27 October of the election year; and identify the myths and communication strategy employed in the candidate’s speech on Twitter platform. It was possible to conclude that Bolsonaro aligned his narrative on Twitter to the aspirations of the Personas that composed the new right, establishing in the scope of this study at least nine strategies, based on the storytelling tool: the hero to be combated; the formulation of enemies; coherence in the development of their story; the backward narrative; the only possible hero; the captain’s metaphor against violence; transmidiatic discourse; sophisticated stimuli and the symbology of green and yellow